DA'WAH OF BANYUMAS ISLAMIC CHINESE ETHNICITY IN THE DEVELOPMENT OF RELIGIOUS MODERATION - Musmuallim Musmuallim; Ahmad Yusuf Prasetiawan; Muhamad Riza Chamadi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
This research focuses on the ethnic-based da'wah model of the Chinese Muslim community who is members of the Indonesian Chinese Islamic Association (PITI) Banyumas in promoting religious moderation. The Banyumas Chinese Muslim community chooses the middle path and contributes to religious moderation through various da'wah activities. This research method uses documentation, interviews, and observations. The results of this study describe an ethnic-based da'wah model through structural and cultural da'wah movements. The da'wah developed promotes a moderate attitude with a socio-economic and socio-cultural approach. Ethnic Chinese who have recently embraced Islam (mualaf) receive training in economic empowerment. The Chinese Muslim community also embodies tolerance in an open attitude towards non-Muslim Chinese ethnicities and various other religious groups. An example of public openness is their acceptance of the Cap Go Meh culture and the lion dance tradition. A moderate attitude is shown by neutrality that is not extreme right and extreme left on the choice of religious schools of thought. PITI places people in the center of society's varieties. Da'wah facilities employ the mosque as a venue for preaching and religious education based on social interaction. Chinese Muslims' preaching through an open, reasonable, and community engagement has been well received by the general public.